AKUNTANSI BERKELANJUTAN DALAM EVALUASI DAN PENGUKURAN KINERJA RANTAI PASOKAN SIRKULAR - Muhammad Helmi Falah; Fety Widianti Aptasari (Jurnal Riset Akuntansi Politala, 2025)
Supply chain transformation towards a circular economy (CE) model is a key strategy in addressing the sustainability crisis caused by linear economic practices. CE offers a new paradigm that balances economic achievement with social and environmental responsibility. However, the implementation of Circular Supply Chain (CSC) still faces challenges, especially in terms of performance evaluation and measurement. One of the main obstacles is the lack of agreement on indicators that can assess sustainability comprehensively at the supply chain level. This study examines the role of sustainable accounting as a strategic information system to support transparency and accountability in CSC performance measurement. Through a literature study, this study maps CE indicators used in academic studies and industry practices. The results show that existing indicators are still fragmented and have not fully integrated economic, environmental, and social dimensions. As a contribution, this study proposes two composite indicators designed to provide a more holistic picture of CSC performance. This framework is expected to support more effective decision-making and encourage the transition towards a sustainable circular supply chain.